The Role of Mindfulness in Reducing Organizational Change Stress: A Qualitative Analysis of a Fintech Company - Dipoatmodjo, Tenri Sayu Puspitaningsih (Journal Management & Economics Review (JUMPER), 2025)
This qualitative study explores the role of mindfulness in mitigating organizational change stress within a fintech company. Through in-depth interviews with 25 employees undergoing significant transitions, the research reveals that mindfulness practices enhance emotional regulation, foster adaptability, and improve team dynamics during periods of change. Participants reported that mindfulness created a "psychological pause button," helping them respond to stressors with greater clarity and resilience. However, the study also identifies limitations- mindfulness showed reduced effectiveness during existential threats like layoffs, and many employees struggled to maintain consistent practice during peak stress. The findings suggest that mindfulness initiatives are most impactful when integrated into daily workflows as micro-practices and supported by team-based approaches. This research contributes to the growing literature on workplace mindfulness by providing nuanced insights into its benefits and challenges during organizational change, particularly in high-pressure industries like fintech.